2018
DOI: 10.3233/wor-182814
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pain psychological factors and job stress in rehabilitation workers with or without chronic pain

Abstract: BACKGROUND: Pain is affected by pain psychological factors (PPFs), whereas relationship between PPFs and job stress are unclear. OBJECTIVE: This study aimed to elucidate the relationship between PPFs and job stress in workers. METHODS:The study participants were the staff of the rehabilitation department of a core hospital. After undergoing a preliminary survey (38/43, 88% response rate), the rehabilitation workers were divided into the chronic pain group (CPG, n = 18) and the nonpain group (NPG, n = 13). RESU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In addition, in the multiple regression analysis, CPG-depression had anxiety as an independent variable, and NPG-anxiety had depression as an independent variable. This finding emphasizes earlier findings that depression is important to consider in cases of chronic pain, while anxiety is an important consideration in the absence of pain [16]. However, this finding may also simply involve the effects of participants’ differential abilities to deal with high stress, as CPG scores were significantly higher in the comparison of the two groups.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In addition, in the multiple regression analysis, CPG-depression had anxiety as an independent variable, and NPG-anxiety had depression as an independent variable. This finding emphasizes earlier findings that depression is important to consider in cases of chronic pain, while anxiety is an important consideration in the absence of pain [16]. However, this finding may also simply involve the effects of participants’ differential abilities to deal with high stress, as CPG scores were significantly higher in the comparison of the two groups.…”
Section: Discussionsupporting
confidence: 82%
“…Accordingly, the results of the present study contribute to the understanding of differences in job-life satisfaction affecting job-related psychological stress between people with chronic pain and those with no pain. Our interpretation that magnification increases depression is appropriate; while the differences regarding the PCS subscales were slight, several studies have reported the importance of magnification as a psychological factor [16,36]. Furthermore, pain catastrophizing and depression have additive and adverse effects on the impact of pain, hence both are important assessment measures for chronic pain [31].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In Japan, women workers are more dominant in the health and welfare industry, followed by retail and wholesale, where low back pain is the most frequently observed health issue. This review found that pain associated with lumbago decreases work engagement 80 and increases psychological distress 81 . As muscle‐required jobs may incur an unexpected burden on health, especially in women, more interventional studies should be warranted to alleviate work‐related physical problems.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, during the lockdown, many individuals could not continue working, which resulted in socio-economic problems and emotional dysfunction (see e.g., [22]). In turn, this has been associated with a worsening of chronic pain, in general (see e.g., [23]). Interestingly, Toprak and colleagues found that individuals who stayed at home during lockdown reported higher levels of low back pain than those who continued going to work [24].…”
Section: Introductionmentioning
confidence: 99%